Dampak Inovasi Produk dan Affiliate Marketing Terhadap Kepercayaan Konsumen dan Minat Pembelian Ulang Scarlett Pada Generasi Z di Semarang - Elvira, Jihan Vivid; Amilahaq, Farikha (Universitas Muria Kudus, 2025)
The development of the skincare industry in Indonesia is growing rapidly with increasing product innovation and digital marketing strategies. One of the strategies used is affiliate marketing which utilizes social media platforms such as TikTok Shop. This study aims to analyze the effect of product innovation and affiliate marketing on consumer trust and repurchase interest. The research method used is quantitative with purposive sampling technique, namely researchers determine certain criteria to select users who will be used as respondents. The data used in this study are primary data from 100 respondents of generation Z scarlett users in Semarang. The data were obtained through a questionnaire and analyzed using SPSS statistical software and to test the effect of intervening variables used the sobel test. The results showed that product innovation has a positive and significant effect on consumer trust and repurchase interest. In addition, affiliate marketing also has a positive and significant effect on consumer trust and repurchase intention. Consumer trust is proven to be a mediating variable between product innovation and affiliate marketing on repurchase intention. This research provides implications for companies in designing more effective marketing strategies to increase consumer loyalty.